Palaeogeographic Distribution of Arenigian (Lower Ordovician) Conodonts - BAGNOLI, GABRIELLA; STOUGE S. (1991)
This paper presents a review of the Paleogeographic distribution of conodont faunas throughout the early Arenigian. According to their geographical distribution the conodont genera have been dividen into five groups: the pandemic Group, the warm water Group including genera belonging to the Midcontinent Province, the cold water Group including genera of the North Atlantic Province, the temperate water Group, and the warm water China Group characterized by an endemic fauna mainly recorded from China and Korea, and their ocuurences has been examined in the different paleocontinents.